THE INFLUENCE OF INFLATION RATE, BI RATE, AND EXCHANGE RATE CHANGES TO THE FINANCIAL SECTOR STOCK PRICE INDEX RETURN IN THE INDONESIAN STOCK MARKET - Yunita Yunita; Robiyanto Robiyanto (Jurnal Manajemen dan Kewirausahaan, 2018)
The objective of this study is to find out how macroeconomic factors such as exchange rate changes, BI rate and inflation rate can affect the financial sector stock price index in IDX from 2011 until 2017. Generalize Autoregressive Conditional Heteroscedasticity (GARCH) is used as the analysis method in this research to find the fittest model. The results are, only exchange rate change that has significant effect to financial sector stock price index. Inflation and BI rate have no significant effect to financial sector stock price index.